An augmented reality approach for supporting panel alignment in car body assembly. (April 2021) - Dalle Mura, Michela; Dini, Gino
Highlights: Development of AR system for supporting operators during panel fitting tasks in car body assembly. Algorithm able to convert gap and flush values between car panels into instructions for operators. Immediate detection of alignment errors with in-process selection of the recovery procedure. Real-time accurate guidance for reduced time and procedural errors in tasks execution. Easy use, thanks to the integration of the real environment and the AR instructions. Abstract: One of the major problems in automotive assembly consists in achieving alignment within the specified tolerances between car panels that make up the exterior bodywork. To reduce errors and time requested to perform the assigned assembly tasks, workers should be guided during these panel fitting operations. Augmented Reality (AR) could be particularly suitable in this regard, as it represents one of the most promising tools to support personnel, with constantly growing applications in production processes. Following this trend, the present work aims to present an AR prototype system for supporting the operator during panel fitting operations of car body assembly, by providing instructions to correct alignment errors in terms of gap and flushness. A real case study concerning the fine alignment of car body panels with respect to the front light projector is also presented.